2012
DOI: 10.4172/2329-6577.1000104
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Calcitriol to Inflammatory Breast Cancer Tumors and Metastasis In Vitro and In Vivo

Abstract: Inflammatory Breast Cancer (IBC) is arguably the most severe form of breast cancer with a very high mortality rate. IBC is distinct from other forms of breast cancer expressing unique cell surface markers such as hypoglycosylated MUC1. However, treatment options for IBC are limited. Calcitriol is a potential treatment for IBC due to its promising role as a therapeutic in other forms of cancer. Our previous research demonstrated that calcitriol inhibits the metastatic ability of the SUM149 IBC cell line. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The antiproliferative effects are thought to be a result of calcitriol blocking the mitogenic effects of insulin‐like growth factor I through downregulation of its receptors, causing the G1 phase of the cell cycle to pause . In addition, it was found that SUM149 cells exposed to calcitriol exhibited a decreased ability to migrate, invade, and form tumor emboli, leading to decreased metastasis in vivo . However, previous studies have required toxic dosages of calcitriol (over 0.50 μg) to have a significant effect, which would lead to hypercalcemia .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The antiproliferative effects are thought to be a result of calcitriol blocking the mitogenic effects of insulin‐like growth factor I through downregulation of its receptors, causing the G1 phase of the cell cycle to pause . In addition, it was found that SUM149 cells exposed to calcitriol exhibited a decreased ability to migrate, invade, and form tumor emboli, leading to decreased metastasis in vivo . However, previous studies have required toxic dosages of calcitriol (over 0.50 μg) to have a significant effect, which would lead to hypercalcemia .…”
mentioning
confidence: 99%
“…In addition, it was found that SUM149 cells exposed to calcitriol exhibited a decreased ability to migrate, invade, and form tumor emboli, leading to decreased metastasis in vivo . However, previous studies have required toxic dosages of calcitriol (over 0.50 μg) to have a significant effect, which would lead to hypercalcemia . Therefore, targeting methods are required to reach desired levels of calcitriol at treatment sites without having an excess of calcitriol in the rest of the body.…”
mentioning
confidence: 99%
See 3 more Smart Citations